Phosphorus sensitivity in species of Proteaceae (Protea obtusifolia, Leucadendron coniferum and Leucadendron salignum) from different soil habitats : possible candidates for growth on former agricultural soils high in P - Harris, Sue-Re (Department of Biological Sciences, 2017)
The phosphorus (P) uptake capacities and tolerance to high P of three Proteaceae species from acid (Leucadenron coniferum, Leucadendron salignum) and alkaline (Protea obtusifolia, Leucadedndron meridianum) soils in the Cape Floristic Region (CFR) were compared. These species were also investigated as potential candidates for growth on nutrient enriched, post-agricultural soils. In parallel, two crop plant species (Lupinus albus, with cluster roots; and L. angustifolius, without cluster roots) were also compared. The cluster-root forming species (L. albus) was more sensitive to higher P levels and showed toxicity in terms of photosynthesis, efficiency of PSII, transpiration and stomatal conductance. Growth, gaseous exchange and efficiency of photosystem II (as a measure of stress) were determined at 1, 10 and 100 μg P g⁻¹ sand for both lupins and Proteaceae. Kinetics of P uptake (in hydroponics) was determined at a range ( 4 to 2000 μM P) of P concentrations. Phosphorus sensitivity was relatively high in Ld. coniferum as evident from reduced growth, net photosynthetic rate, stomata} conductance and transpiration rates. Protea obtusifolia showed the least sensitivity to increased phosphorus concentrations under acidic and native alkaline conditions. The inability to regulate P uptake rates at elevated phosphorus concentrations and excessive P accumulation were major determinants of P sensitivity. The relatively higher P sensitivity of Lupinus albus compared to L. angustifolius is likely related to the efficient P uptake by cluster roots in the former.